Difference in weight gain among breast-fed and mix-fed infants at 6 weeks - Kaur, Akhil Preet; Dhar, Sharvil; Khajuria, Anmol; Gupta, Ravinder K.; Rana, Wajid (International Journal of Contemporary Pediatrics, 2025)
Background: Breastfeeding practice protects children from a large number of illnesses, increases IQ and improves a strong bond between mother and infant. Body weight is an important sign of a baby’s growth and development. The relationship between breastfeeding and body weight is crucial for the wellbeing of neonates. Methods: This cross-sectional study was conducted at Department of Paediatrics, ASCOMS, Jammu for a period of 06 months. In the study 200 neonates were included and divided into two groups on the basis of self-reported feeding mode (breast-feeding and mix-feeding). History on maternal parameters and infant parameters at birth and 06 weeks were noted on a pre-designed proforma. The data was recorded in Microsoft excel sheet and was analysed by SPSS 20.0 version. Results: It has been observed in our study that none of the maternal parameters significantly differed among the two feeding modes (Breast fed and mix-fed). Out of 100 breastfed infants 45% had weight 4.0-4.2 kg, 32% had weight 4.2-4.4 kg, 14% had weight >4.4 kg and 9% had weight<4 kg. Out of mix-fed infants 48% had weight 4.0-4.2 kg, 28% had weight 4.2-4.4 kg, 10% had weight >4.4 kg and 14% had weight<4 kg. Further, the weight gained by infants at 06 weeks after birth slightly differed with breastfed infants having slightly more weight gain as compared to mix-fed infants. Conclusions: The current study found slight difference in weight gain between infants who were exclusively breastfed and those who were mix-fed at 06 weeks of life.